Placental Vasculogenesis Is Regulated by Keratin-Mediated Hyperoxia in Murine Decidual Tissues - Kröger, Cornelia (American Society for Investigative Pathology, 2011)
The mammalian placenta represents the interface between maternal and embryonic tissues and provides nutrients and gas exchange during embryo growth. Recently, keratin intermediate filament proteins were found to regulate embryo growth upstream of the mammalian target of rapamycin pathway through glucose transporter relocalization and to contribute to yolk sac vasculogenesis through altered bone morphogenetic protein 4 signaling. Whether keratins have vital functions in extraembryonic tissues is not well understood. Here, we report that keratins are essential for placental function. In the absence of keratins, we find hyperoxia in the decidual tissue directly adjacent to the placenta, because of an increased maternal vasculature. Hyperoxia causes impaired vasculogenesis through defective hypoxia-inducible factor 1α and vascular endothelial growth factor signaling, resulting in invagination defects of fetal blood vessels into the chorion. In turn, the reduced labyrinth, together with impaired gas exchange between maternal and embryonic blood, led to increased hypoxia in keratin-deficient embryos. We provide evidence that keratin-positive trophoblast secretion of prolactin-like protein a (Prlpa) and placental growth factor (PlGF) during decidualization are altered in the absence of keratins, leading to increased infiltration of uterine natural killer cells into placental vicinity and increased vascularization of the maternal decidua. Our findings suggest that keratin mutations might mediate conditions leading to early pregnancy loss due to hyperoxia in the decidua.